2009
DOI: 10.1038/ejhg.2008.268
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 13q13–q14 locus overlaps mood and psychotic disorders: the relevance for redefining phenotype

Abstract: The nosology of major psychoses is challenged by the findings that schizophrenia (SZ) and bipolar disorder (BP) share several neurobiological, neuropsychological and clinical phenotypic characteristics. Moreover, several vulnerability loci or genes may be common to the two DSM disorders. We previously reported, in a sample of 21 kindreds (sample 1), a genome-wide suggestive linkage in 13q13 -q14 with a common locus (CL) phenotype that crossed the diagnostic boundaries by combining SZ, BP and schizoaffective di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 66 publications
(46 reference statements)
7
25
0
Order By: Relevance
“…Some of the results obtained coincide with linkage signals previously obtained in our sample 8 and also detected in other studies such as the signal on chromosome 13q that has been widely reported in the literature (see a review of 25 studies in DeteraWadleigh and McMahon 18 ), indicating two main zones of linkage with SZ or BP: one in 13q13-q14 (E40 Mb) and another in 13q21-q33 (E95 Mb). Our data suggest that the manic symptom dimension as a phenotype may help to reconcile the findings overlapping SZ and BP from different studies or to better understand the probable heterogeneity at this locus.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Some of the results obtained coincide with linkage signals previously obtained in our sample 8 and also detected in other studies such as the signal on chromosome 13q that has been widely reported in the literature (see a review of 25 studies in DeteraWadleigh and McMahon 18 ), indicating two main zones of linkage with SZ or BP: one in 13q13-q14 (E40 Mb) and another in 13q21-q33 (E95 Mb). Our data suggest that the manic symptom dimension as a phenotype may help to reconcile the findings overlapping SZ and BP from different studies or to better understand the probable heterogeneity at this locus.…”
Section: Discussionsupporting
confidence: 91%
“…In the combined sample, the linkage peak with CL at marker D13S1297 (42.1Mb) reached a parametric MOD score of 3.12 and an NPLpair Àlog 10 P-value of 5.21, exceeding that obtained in each sample and indicating consistency across the two samples. 8 Using our subtyping strategy, we found a significant linkage signal replicated across samples at marker D13S291 (44.82 Mb) reaching a MOD score of 5.20 on the second subtype identified from the mania dimension (Table 3), corresponding to a P-value of 1.0 Â 10 À6 or Àlog 10 P-value of 6.0. As seen in Figure 1a (mania subtype 2), this subtype represents a cluster of 323 subjects expressing manic symptoms (ie, who had at least a questionable level of manic symptoms).…”
Section: Identification Of Dimension Subtypesmentioning
confidence: 86%
See 1 more Smart Citation
“…Our group and others have extensively documented commonalities in mechanisms across SZ and BP as indicated by their familial co-aggregation [1,17] , neurocognitive and neurobiological endophenotypes [18,19] and several genetic linkage or association signals [2,[20][21][22] . In addition to genes conferring susceptibility to the broad spectrum of MP spanning SZ and BP, we hypothesize that other genes may modify the effect of these genes and lead to the specific expression of either SZ or BP.…”
Section: Translation Of Proposed Methods To Our Sample Of Sz and Bp Kmentioning
confidence: 99%
“…Among the 48 kindreds, we already reported [20] that 12 of the 48 kindreds presented both SZ and BP cases in comparison to the other families that were predominantly affected by either SZ or BP, i.e. no more than 15% of patients were affected by the other disorder in a family.…”
Section: Sample Descriptionmentioning
confidence: 99%